2003
DOI: 10.1177/0269881103017002010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Quetiapine on Depressive Symptoms in Patients with Partially Responsive Schizophrenia

Abstract: While atypical antipsychotics appear to be effective in reducing depressive symptoms in the acute phase of schizophrenia, little is known about their efficacy in patients with ongoing symptoms. The present study assessed whether quetiapine (Seroquel) is more effective than haloperidol in treating depressive symptoms in patients with persistent positive symptoms, and investigated whether this effect is independent, or secondary to, reductions in other symptoms such as positive, negative or extrapyramidal sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
3
38
1
2
Order By: Relevance
“…Although in our knowledge there are no preclinical data supporting a depression indication for QTP, the antidepressant effect of QTP resulting from our experiments is in line with previous clinical studies comparing the efficacy of QTP and risperidone, another atypical antipsychotic drug, for the treatment of depressive symptoms in psychotic outpatients (Sajatovic et al, 2002) or assessing the efficacy of QTP vs haloperidol, a typical antipsychotic, in reducing depressive symptoms in patients with refractory schizophrenia (Emsley et al, 2003). In addition, a retrospective study of Sokolski and Denson (2003) reported significant improvements in clinician-rated bipolar severity scores for mania, depression, and overall bipolar illness after administration of low doses of QTP in patients with incomplete response to mood stabilizers.…”
Section: Discussionsupporting
confidence: 86%
“…Although in our knowledge there are no preclinical data supporting a depression indication for QTP, the antidepressant effect of QTP resulting from our experiments is in line with previous clinical studies comparing the efficacy of QTP and risperidone, another atypical antipsychotic drug, for the treatment of depressive symptoms in psychotic outpatients (Sajatovic et al, 2002) or assessing the efficacy of QTP vs haloperidol, a typical antipsychotic, in reducing depressive symptoms in patients with refractory schizophrenia (Emsley et al, 2003). In addition, a retrospective study of Sokolski and Denson (2003) reported significant improvements in clinician-rated bipolar severity scores for mania, depression, and overall bipolar illness after administration of low doses of QTP in patients with incomplete response to mood stabilizers.…”
Section: Discussionsupporting
confidence: 86%
“…Although a recent meta-analysis showed no superior effect of QTP to conventional antipsychotic drugs in the treatment of negative symptoms (Schulz et al, 2003), the low rate of EPS may be related to the reduction of secondary negative symptoms. Some studies have shown a greater effect of QTP on depressive symptoms compared with haloperidol (Emsley et al, 2003) or risperidone (Mullen et al, 2001). The present study with a small number of subjects, however, did not show any correlation between the changes in the scores of QLS or SQLS and the changes in the scores of negative or depressive symptoms from baseline to the end of study (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
“…These findings are consistent with previous studies reporting the effect of quetiapine on depressive symptoms in patients with acute or chronic schizophrenia (Arvanitis et al, 1997;Khouzam, 2000;Emsley et al, 2003;Kasper, 2004). Emsley et al compared the efficacy of quetiapine with haloperidol for patients with a history of partial response to conventional antipsychotic, and reported that quetiapine produced a greater reduction in depression scores (PANSS depression factor) than haloperidol (À1.6 vs. À0.54) (Emsley et al, 2003). Patients with higher depression scores (PANSS depression factor score of !…”
Section: Discussionsupporting
confidence: 93%
“…In one brief report, quetiapine was superior to placebo in improving depressive signs and symptoms in patients with schizophrenia (Arvanitis et al, 1997). In a study of partial responders to conventional antipsychotic agents, the switch to quetiapine produced a significant reduction in the positive and negative syndrome scale (PANSS) depression factor which was interpreted to be a direct effect on depressive symptoms (Emsley et al, 2003). A recent analysis of data from the open-label extension phases of three randomized clinical trials demonstrated that quetiapine was effective for the treatment of depressive and anxiety symptoms in longterm treatment (Kasper, 2004).…”
Section: Introductionmentioning
confidence: 99%